FEATURES OF PAPILLOMAVIRUS INFECTION IN HUMAN IMMUNODEFICIENCY VIRUS-INFECTED WOMEN - KRISTINA V. Marochko; NATALIA V. Artymuk (Фундаментальная и клиническая медицина)
Aim. To determine prevalence and features of human papillomavirus (HPV) infection in human immunodeficiency virus (HIV)-infected women.Materials and Methods. We recruited 150 imprisoned women aged 25 to 59 years (mean age 37.3 ± 8.0) following clinical examination and analysis of medical documentation including HIV status. Identification of high-risk HPV strains (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59) was carried out using real-time polymerase chain reaction. Results. High-risk HPV strains, particularly HPV-16, -39, and -52, were detected in 58.2% of HIV-infected and 23% of HIV-negative women (p < 0.001). Furthermore, the combination of ≥ 4 HPV genotypes was more prevalent in HIV-infected women (p = 0.043). Strikingly, HIV-infected women with shorter duration of HIV-infection and/or taking antiretroviral treatment were less frequently infected with high-risk HPV (p < 0.05).Conclusions. A significant proportion of HIV-positive women is infected with HPV-16, -39, -52, or combination of ≥ 4 HPV strains.